Estimation of serum zinc levels in children with febrile convulsions - H., Ubaidur Rehman; Khan, Shamshad Ahmed; Saldanha, Prakash R. (International Journal of Contemporary Pediatrics, 2018)
Background: Febrile seizures are the most common form of convulsion in children with the aged between 6 months to 6 years. Diﬀerent studies have shown that reduction of zinc leads to the incidence of febrile seizures in children. This study was conducted with the goal of examination of the zinc level in the patients with Febrile Seizures. Methods: This cross sectional study was conducted on 50 children in two equal groups of children with febrile seizures, febrile children without seizures. In order to examine the zinc level blood samples were taken of all subjects and the zinc level of these patients was determined. The data was analyzed using the SPSS-16 statistical software and by descriptive statistical tests. Results: 31 males (47.2%) and 19 female children (52.8%) with the average age of 27.23±15.3 months were examined. The two groups had no signiﬁcant diﬀerence in terms of age and sex. The average of zinc level in the patients with Febrile Seizures was 57.4 µg/dL and it was 116 µg/dL in the febrile children without FS there was a signiﬁcant diﬀerence between the two groups in terms of the zinc level (P=0.01). Conclusions: The low serum zinc level in the group of patients with Febrile Seizures compared with children without febrile seizures indicate the existence of a relationship between the serum zinc level and development of FS in children aged between 6 months and 6 years.